How a learning organization cultivates self-directed learning - Ida Juliana, Hutasuhut; Shahren, Ahmad Zaidi Adruce; Victoria, Jonathan (Emerald Publishing Limited, 2021)
Purpose This study aims to provide empirical evidence of how the five disciplines of learning organization introduced by Senge (1990) are practiced and how it could cultivate self-directed learning among employees.